2019
DOI: 10.1111/obr.12768
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition‐related interventions targeting childhood overweight and obesity: A narrative review

Abstract: Systematic reviews of nutritional interventions indicate limited efficacy in reducing childhood obesity, but their blanket conclusions could obscure promising components.This narrative review sought more detail on effective components within nutritionrelated interventions involving children aged 2 to 11 years. In May 2016, the World Health Organization (WHO) searched the Cochrane Library and PubMed for relevant reviews. From 36 reviews, we screened 182 nutrition-related randomized trials for inclusion. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…They were able to identify components that proved effective, which included adaptations to the school environment. However, even in this selection of trials, effects were rather small [54]. Accordingly, Brown et al.…”
Section: School-aged Children (6–12 Years Old)mentioning
confidence: 82%
See 1 more Smart Citation
“…They were able to identify components that proved effective, which included adaptations to the school environment. However, even in this selection of trials, effects were rather small [54]. Accordingly, Brown et al.…”
Section: School-aged Children (6–12 Years Old)mentioning
confidence: 82%
“…They were able to identify components that proved effective, which included adaptations to the school environment. However, even in this selection of trials, effects were rather small [54]. Accordingly, Brown et al [52 && ], within their Cochrane review meta-analysis, found high-certainty evidence from 15 RCTs that isolated dietary interventions had no effect on BMI or zBMI.…”
Section: Nutrition Among School-aged Childrenmentioning
confidence: 97%
“…Nutrition-based interventions include increasing access to fruits and vegetables, limiting intake of sugar-sweetened beverages, minimizing fat content in meals, adjusting nutrition standards in schools, and educating families about healthy nutrition practices [67][68][69]. Thus far, the efficacy of such treatments has been limited, showing only modest success in reducing BMI and other obesity related factors [67,68,70]. Multi-component interventions demonstrate similar results, although research suggests programs with environmental components have the potential to produce larger, long-term changes [68,[71][72][73].…”
Section: Treatment Nutritionmentioning
confidence: 99%
“…Thus far, the efficacy of such treatments has been limited, showing only modest success in reducing BMI and other obesity related factors [67,68,70]. Multi-component interventions demonstrate similar results, although research suggests programs with environmental components have the potential to produce larger, long-term changes [68,[71][72][73]. This evidence emphasizes the need for additional research to determine if nutrition-related treatment options could provide longer-lasting positive health outcomes in children and adolescents with obesity.…”
Section: Treatment Nutritionmentioning
confidence: 99%
“…Open access reported from obesity prevention intervention studies in children aged from birth to 5 years. [5][6][7] There are also a wide range of methods currently used for measuring relevant outcomes, which limits consistency and comparability of findings between studies and can lead to research waste. 8 Variation also makes evidence synthesis via retrospective meta-analysis very difficult, if not impossible, due to limitations in combining data that has been collected, measured or reported using different methods.…”
Section: Introductionmentioning
confidence: 99%